Disclosure in the annual reports of Australian government departments: A research note - Herawaty, Merry; Hoque, Zahirul (Journal of accounting & organizational change, 2007)
Annual reports are perceived to be important sources of information about government departments' performance, accountability, efficiency and effectiveness. This paper aims to report on an empirical study that explores the current disclosure practices by Australian government departments. To achieve the research aim, the paper assesses the 2005-2006 annual reports of 56 Australia Government departments. It analyses 47 mandatory disclosures and 20 voluntary disclosures reported by the subject organizations. It employs a disclosure index to calculate the level of disclosures. The findings reveal that the voluntary disclosure level is higher than the mandatory disclosure in the subject departments. Further, it is found that the annual reports of government departments reveal a low level of disclosures in the areas of human resources, asset management, external scrutiny, purchasing, and contracting. The study is based on published annual reports only. Therefore, it provides little in-depth insights into the current disclosure practice within the subject organizations. The findings reported in this paper will be of value to both theoretical and empirical studies of how organizational and institutional forces may affect the level of disclosure in the annual reports of public sector organizations. The study will provide basis for further research into this area in various international settings. Practically, this study will assist government departmental management to continue improving their quality of reporting.